THE CORRELATION BETWEEN CRITICAL THINKING AND WRITING ABILITY AMONG ENGLISH DEPARTMENT STUDENTS AT STKIP YAYASAN ABDI PENDIDIKAN - Wati, Refna (ELP (Journal of English Language Pedagogy), 2024)
Some studies have revealed that critical thinking is related to language proficiency. This research examined the correlation between critical thinking and writing ability in English. This correlational study involved 44 students from the English educational program at STKIP Abdi Pendidikan Payakumbuh who had taken the general writing subject, using total sampling. The instruments included a questionnaire to assess students' critical thinking and official academic records for writing scores. The Pearson Product Moment formula was used to analyze the data. Results indicated a significant positive correlation (r_xy = 0.362, p < 0.05), confirming that critical thinking skills are related to writing ability. This finding highlights that writing, which involves the clear articulation of ideas, constructing arguments, and presenting evidence, inherently requires critical thinking skills.